2021
DOI: 10.46328/ijres.1594
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Skills and Problem-Solving

Abstract: The purpose of this study is to investigate the metacognitive strategies that middle school students used in the process of solving problems individually. The study group consisted of 37 middle school students in the eighth grade. The students were asked one non-routine word problem, and their written answers were collected. After solving the problem, the students filled out a self-monitoring questionnaire that requested them to reflect retrospectively on the metacognitive strategies they employed for the prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 46 publications
1
16
0
1
Order By: Relevance
“…The students' responses to reveal the influence of using MTS; the high the MTS levels the better the communication skills. These findings are consistent with other studies in literature (Guner & Erbay, 2021). In this study students were evaluated in all three fluencies of communication-digital, writing and speaking using oral presentations, PowerPoint and written reports.…”
Section: Metacognitive Skills (Mts)supporting
confidence: 91%
See 1 more Smart Citation
“…The students' responses to reveal the influence of using MTS; the high the MTS levels the better the communication skills. These findings are consistent with other studies in literature (Guner & Erbay, 2021). In this study students were evaluated in all three fluencies of communication-digital, writing and speaking using oral presentations, PowerPoint and written reports.…”
Section: Metacognitive Skills (Mts)supporting
confidence: 91%
“…Articulation (Communication) Skills: Researchers through the years, have stated that students who have increased their MTS levels will be much better at understanding what they read and consequently this shows in how they solve problems as well as how they articulate their responses (Guner & Erbay, 2021). The students' responses to reveal the influence of using MTS; the high the MTS levels the better the communication skills.…”
Section: Metacognitive Skills (Mts)mentioning
confidence: 99%
“…Metacognition skills need to be developed in the learning process in the classroom accompanied by the teacher. In the learning process, metacognitive skills have a significant direct effect on the problemsolving abilities faced by students where it appears that students are more enthusiastic in solving problems correctly through appropriate strategies and logical reasons, it can be concluded that students' perceptions of their performance affect their ability to monitor the learning process (Avargil et al, 2018;Güner & Erbay, 2021). Based on the analysis and research findings, it can be concluded that an increase in students' metacognitive abilities can improve their learning outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…Literatürde öğrencilerin üstbilişsel farkındalık düzeylerini belirlemeye yönelik çalışmaların (Ağpak, 2019;Arslan, 2020) yanı sıra üstbilişin; problem çözme (Arum vd., 2019;Güner & Erbay, 2021), öz-yeterlik, akademik başarı gibi (Demir, 2013) bilişsel süreçlerle ve problem kurma (Divrik vd., 2020;Ghasempour vd., 2013;Nicolaou & Philippou, 2007) ile ilişkisini belirlemek için yapılan çalışmalar yer almaktadır. Söz konusu bu çalışmaların dışında matematiksel üstbiliş farkındalığı ile problem kurma özyeterliği değişkenleri arasındaki ilişkiyi inceleyen bir çalışmaya ulaşılamamıştır.…”
Section: Problem Kurma öZ-yeterlik Algısıunclassified